Substantiation of conditions of maintaining stability of haulage drifts during development of steep seams - Iordanov, Igor; Simonova, Yuliia; Novikova, Yuliia; Korol, Anton; Podkopayev, Yevgen; Kayun, Oleksiy (Technology audit and production reserves, 2020)
The object of research is the processes of ensuring the stability of lateral rocks in haulage drifts during the development of steep coal seams. With an increase in the depth of mining, the applied methods of protecting local preparatory excavations should ensure their operational condition in the excavated areas and correspond to changing mining and geological conditions within the mine field. Investigations of the manifestations of rock pressure in haulage drifts along the length of the excavation section are performed under field conditions. At specially equipped metering stations, the displacement of the lateral rocks on the preparatory excavation circuit is determined. The haulage drift is protected by rolling bonfires made of wooden sleepers or coal pillars. In the course of research, the influence of the stiffness of protection structures on the stability of lateral rocks in the haulage drift is established. A linear relationship is recorded between the displacements of the roof rocks and the load on the lining in the excavation along the length of the excavation section while protecting the haulage drift by the coal pillars. At the same time, with a decrease in the stiffness of the pillars by 80 %, the section of the haulage drift decreases by 50 % from the initial one. It is noted that the use of wooden structures for protection structures allows to limit the displacement of rocks on the contour of the haulage drift. As a result of the interaction of lateral rocks with wooden protection structures, with a decrease in their stiffness by 80 %, the section of the haulage drift decreases by 30–35 % from the initial one. Studies have shown that the reduction in the stiffness of wooden structures occurs due to their compression, and the coal pillars – as a result of destruction. It is noted that the most difficult conditions for maintaining haulage drifts are formed when using coal pillars. It is recommended, to ensure the stability of local preparatory workings, the use of compliant protection structures or the laying of excavated space. The obtained research results can be used when choosing a method for protecting haulage drifts on steep coal seams